Family Bonding and Its Impact on Self-Esteem An Explorative Study on the Impact of an Individual’s Self–Esteem on Performance: Exploring the Role of Family Bonding in Shaping Self-Esteem during Adolescence (Journal of Advances and Scholarly Researches in Allied Education, 2018)
One of the most crucial periods of the life of an individual is adolescence. During this period, individual faces many problems because of hormonal changes due to onset of puberty, such as feeling of depression, loneliness, anxiety, inferiority complex etc. all this affects the self-esteem of a person. Self-esteem can be influenced by many factors such as school, friends, and inner personality, but in early childhood and adolescence period the family plays a crucial role in shaping self-esteem. Therefore, the present study is aimed to determine the Relationship between family bonding and its impact on self-esteem.